Business Model Evolution: From Traditional to Digital Transformation - Sacha, Shinta; Wardani, Febri Pramudya; Krismayanti, Yanti; Fauziah, Fachrizah; Krisnadi, Tasya Widya; Nauvaldy, Daffaa; Suherman, Trisya; Tangkudung, Audrey Gamaliel Dotulong (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digital transformation has significantly changed the business landscape, bringing a huge impact on traditional business models. This research aims to explore the evolution of business models from the traditional era to the era of digital transformation. Through focus group discussions (FGDs) with participants consisting of various business stakeholders, this research identifies key factors driving digital transformation, challenges faced by traditional businesses, as well as opportunities arising from the adoption of digital technologies. The results showed that technological innovation, changing consumer behavior, and the need for operational efficiency are the key drivers of digital transformation. The research also underscores the importance of adaptation strategies and digital competency development for success in the digital age. The findings provide important insights for business practitioners and academics in understanding the dynamics of business model change in the era of digital transformation